Homicídios e desorganização social: o caso de Belo Horizonte - Rafael Augusto Reis da Mata; Alexandre M. A. Diniz; Antônio Hot Pereira de Faria (Confins)
This article investigates the relationship between socioeconomic characteristics of the population of Belo Horizonte, taken from the demographic indicators of the 2010 census, and homicide crimes recorded in the same year, in addition to counting on the districts of the municipality as a spatial clipping for the analysis. The Theory of Social Disorganization was used as a basis, where we consider the hypothesis that urban networks and local communities contribute to the process of socialization of the individual and that when communities suffer from socioeconomic vulnerability, social control is difficult, which may condition criminal behavior. Through correlation and linear regression analyses, a direct relationship was found between the occurrence of homicides and most socioeconomic indicators, confirming the hypothesis of the research.